Respon Masyarakat Terhadap Kebijakan Larangan Membeli BBM Menggunakan Jerigen di SPBU Desa Pengalihan Kecamatan Keritang Kabupaten Indragiri Hilir - Wahab, Abdul; Yusuf, Yusmar (Journal of Management Education Social Sciences Information and Religion, 2025)
This research aims to analyze the community's response to the policy prohibiting the purchase of fuel using jerrycans at the gas station in Pengalihan Village, Keritang District, Indragiri Hilir Regency. This policy was implemented to prevent the hoarding and misuse of subsidized fuel, but it has a significant impact on the activities of palm oil farmers who rely on biosolar fuel. The research employs a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that the majority of the community does not understand the basis of the policy and experiences difficulties in obtaining fuel. This policy has caused unrest and affected the productivity of palm oil farmers. The conclusion of this research is that the lack of socialization has led to negative responses and issues in the policy's implementation.